Environmental Reporting and Management in Africa - Tauringana, Venancio (Advances in Environmental Accounting and Management Ser., 2019)
Environment management and protection are top global priorities, but little is known about the reporting in regions of Africa. The six papers in this volume provide much needed information for academics, practitioners and policy makers about environmental accounting and management in Africa.